Meningkatkan Kinerja Karyawan Melalui Penguatan Kompetensi Kerja - Selvi Zola Fenia; Yeki Candra (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
This study aims to examine the influence of work experience and work motivation on employee performance with work competence as a mediating variable at PT TEU. A quantitative approach was employed using a survey method, and data were collected through questionnaires distributed to employees across various divisions. The data were analyzed using Structural Equation Modeling (SEM) to assess both direct and indirect effects among variables. The findings indicate that work experience and work motivation have a positive and significant effect on work competence. Additionally, both work experience and motivation significantly improve employee performance. Work competence is also found to play a mediating role in strengthening the relationship between work experience and motivation toward employee performance. These results highlight the importance of enhancing employee competence as a strategic effort for improving overall performance within the company. The study provides practical implications for organizational management in developing targeted training and motivation programs.